The causal link between trade openness and government size: Evidence from the five largest economies in Africa - Taofik Mohammed Ibrahim (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - The purpose of this paper is to examine the causal link between trade openness and government size for the five largest economies in Africa taking into account the role of compensation hypothesis in an economy. Design/methodology/approach - Time series data for five countries covering the period 1970 to 2010 was used for the analysis. The data was obtained from Penn table and World development indicator (WDI). The causality test adopted for this study is based on the ECM framework. This was done for each of the five countries selected. Findings - Empirical evidence show a positive causal link between trade openness and government size for Nigeria and Algeria. In the case of South Africa negative causality was found while there was no causality for Angola and Egypt. Therefore, the government of these countries need to spend productively in order to cushion the effect of exposure to risks. Research limitations/implications - The need to consider the sustainability of growth due to increasing demand for African countries to diversify their economy in order to take advantage of its export potential and enjoy the gains of trade led to the consideration of the five largest economies in Africa. However, the same causality approach can be applied for other African countries. Originality/value - The results tend to support the existence of compensation hypothesis for Nigeria and Algeria.
Keywords: F41; H11; 330; Compensation-Hypothesis; Algeria; Angola; Egypt; South Africa; Nigeria